-2z2+8=0

Subtract 8 from both sides of the equation.

-2z2=-8

Divide each term in -2z2=-8 by -2.

-2z2-2=-8-2

Cancel the common factor of -2.

Cancel the common factor.

-2z2-2=-8-2

Divide z2 by 1.

z2=-8-2

z2=-8-2

Divide -8 by -2.

z2=4

z2=4

Take the square root of both sides of the equation to eliminate the exponent on the left side.

z=±4

Simplify the right side of the equation.

Rewrite 4 as 22.

z=±22

Pull terms out from under the radical, assuming positive real numbers.

z=±2

z=±2

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

z=2

Next, use the negative value of the ± to find the second solution.

z=-2

The complete solution is the result of both the positive and negative portions of the solution.

z=2,-2

z=2,-2

z=2,-2

Solve for z -2z^2+8=0